Seroprevalence of Hepatitis B and C Viruses among Blood Donors in Sulaimani Major Blood Bank for the Years 2006 and 2007: A Comparative Study - Hussein, Ali Hattem (Sulaimani Journal for Pure and Applied Sciences, 2010)
Background: Hepatitis B (HBV) and C (HCV) viral infections are a serious global public health problem. The objective of this study was to verify the trend of HBV and HCV infections among blood donors in Major Blood Bank of Sulaimani in the years 2006 and 2007. Patients and Methods: The study analyzed the data of blood donors in Sulaimani city who donated blood at Major Blood Bank of Sulaimani during the year 2006 and their correspondence in 2007. HBsAg status was determined by using BIOELISA HBsAg TEST KIT and antibodies to HCV using BIOELISA Anti-HCV TEST KIT. Samples repeatedly reactive for HBsAg or anti-HCV were considered positive for HBV or HCV infection respectively. We set up a hypothesis that to be tested using Chi-Square test at 95% confidence level and degree of freedom equal to one. Results: The overall seroprevalence of HBV infection among donors was 0.48% in 2006 and changed significantly in the next year to 0.25%, (P<0.05). The overall seroprevalence of HCV among donors was 0.11% and did not changed significantly in the next year, (p > 0.05). Significant decrease in HBsAg seroprevalence was particularly seen in non–first time donors in 2007, (p < 0.05). All female donors were negative for HBV and HCV in both years. Conclusion: There are low rates of both HBV and HCV infections among blood donors in 2006 and 2007, HCV is less seroprevalence than HBV, and the decreased rate of HBV infection in 2007 than in 2006 indicates good control of known risk factors. Also, factors that led to zero% of infection among female donors should be clarified and followed.
Keywords: blood donors; Hepatitis B virus; Hepatitis C virus; blood bank; Sulaimani